Final answer:
To find the value of -50 + 5/13p for p = -26, you multiply 5/13 by -26 to get -10, then add this to -50 to get -60.
Step-by-step explanation:
To evaluate -50 + 5/13p when p = -26, you will replace p in the equation with -26 and simplify. First, calculate 5/13 times -26, which is -10. Then add this value to -50 to get the final result.
Steps:
Multiply 5/13 by p (-26): (5/13) x (-26) = -10.
Add this result to -50: -50 + (-10) = -60.
Therefore, the value of the expression -50 + 5/13p when p = -26 is -60.